An ultralow-energy ADC for Smart Dust. - Scott, M.D (IEEE Journal of solid state circuits)
A low-energy successive approximation analog-to-digital converter (ADC) targeted for use in distributed sensor networks is presented. The individual nodes combine sensing, computation, communications, and power into a tiny volume. Energy is extremely limited, forcing the nodes to operate with very low duty cycles. This paper describes the design and implementation of an ADC to meet the unique requirements of sensor networks. The ADC reported here consumes 31 pJ/8-bit sample at 1-V supply and 100 kS/s, with a standby power consumption of 70 pW. This energy consumption is one of the lowest ever reported.